Gamification in Ghanaian mathematics classrooms: Examining the roles of teacher knowledge, motivation, and self-Efficacy on student engagement - Dadzie, Justice; Anaan-Brew, Ruth Keziah; Danso, Elizabeth (American Journal of STEM Education, 2025)
This study aims to investigate how teacher knowledge of gamification, alongside motivation and self-efficacy, shapes student engagement in junior high school mathematics classrooms in Ghana. Drawing upon Bandura’s social cognitive theory, Astin’s theory of involvement, and Tinto’s interactionalist theory, this study addresses the growing demand for innovative, student-centered instruction in resource-constrained educational settings. We employed a cross-sectional survey design and collected data from 155 mathematics teachers using validated instruments. We analyzed the data through structural equation modeling. The results showed that teachers with higher self-efficacy were more likely to adopt gamification strategies, while greater motivation unexpectedly correlated with reduced gamification use. However, both teacher motivation and gamification knowledge significantly enhanced student engagement. We also found that self-efficacy indirectly influenced gamification use through motivation but did not significantly affect student engagement via this pathway. These findings highlight the need to equip teachers with gamification knowledge while addressing complex motivational dynamics. By exploring how teacher confidence and innovation affect student participation, the study offers practical insights for teacher training and policy reform. The research had contributed to the theoretical understanding of gamification in low-resource settings and demonstrated its transformative potential for mathematics education in Ghana.